Limites e possibilidades de contribuição aos processos de integração regional, de-senvolvimento local e combate às desigualdades pelo Instituto Federal de Educação, Ciência e Tecnologia - Silva, Edvaldo Pereira da (Universidade do Vale do Rio dos Sinos, 2016)
The theme of this thesis are Federal institutions located in the northern region of Brazil, as so-cial actors executors of public policy professional education. The objective was to contribute to the understanding of the social process of establishment of such institutions, from the iden-tification of the limits and possibilities of its contribution to regional integration, local devel-opment and the fight against inequality, due to the relevance of its legal definition and the practical effects of its social action. Taking into account the structural conditions and func-tioning of such institutions, the study sought to investigate whether they can actually meet the expectations generated around its creation, according to the perception of their managers. From the context of professional education in the country and the Federal Network in the North, contrasts the assumptions, goals and purposes of these institutions with the structural conditions of their deployment processes and the reality in which they are inserted. The prob-lem investigated puts in evidence among the managers, questioning whether these institutions can really meet the expectations outlined for its social function according to the assumptions of the 11.892/08 law and how they can do it. The theoretical foundation sought references that, recognizing the diversity of social contexts and the complexity of the relationships, di-mensions and factors involved in the structuring and organization of life in society, may sup-port the arguments and considerations of Federal Institutions and their actions. Thus, the complexity and diversity of the issues involved in the problem situation and the dynamics of the social context might be considered in the amplitude of their extensions, as variables that can be influenced, how much influence the dynamics of functioning of such institutions. As methodological procedure three institutes were selected as cases to be studied, the data were collected through questionnaires and conducting interview, systemized and considered in ac-cordance with the procedures of content analysis. In the final considerations is the recognition of the limitations of this study, aware that the subject was not exhausted, but with the convic-tion that the goals were achieved, enabling consistent answers to the problem situation. One arrives at the conclusion that, between the legal provisions and the official discourse there is a dilemma for the Federal Institutes in relation to the senses of its social function, or act as obe-dient and schools meet in their formative processes demands of the productive process, or resize your actions and focus on human development perspectives. In this context, the possi-bility of fulfilling the social function of the Federal Institutes is relative, depending on the di-rections of their social agents and reciprocity, in internal and external contexts. The theme of this thesis is still open, conducive to the realization of other works, including with the partici-pation of social actors have not yet considered.
Keywords: Instituto Federal; Educação profissional; Ação social; Desigualdades; Desenvolvimento local; The Federal Institute; Professional education; Social action; Inequalities; Local development; ACCNPQ::Ciências Humanas::Sociologia